Temporal modulation of duodenal microbiota in dairy cows: effects of dietary shift from high forage to high concentration - Wang, FuWei; Xie, Biao; Ji, Hongjin; Xia, Jianmin; Hao, Yangyi; Cao, Zhijun; Wang, Wei; Gao, Min; Li, Shengli; Yang, Kailun (Frontiers in Veterinary Science, 2025)
IntroductionThe duodenum and its resident microbiota play crucial roles in the process of nutrient digestion and absorption. However, the temporal dynamics of duodenal microbiota in response to different dietary regimes remain are not yet fully understood. The aim of the present study was to explore the effects of high-forage (HF) and high-concentration (HS) diets on the circadian rhythm variation of duodenal fermentation and microbial communities in dairy cattle.MethodsSix duodenum-cannulated Holstein dairy cows were assigned to HF and HS diets according to a crossover design with two periods, with each period lasting 21 d (18 d for adaptation, 3 d for sampling). Duodenal content samples were collected at six time points (07:00, 11:00, 15:00, 19:00, 23:00, and 03:00) for the analysis of volatile fatty acids (VFA) and characterization of microbial characterization. The times of 11:00, 15:00, and 19:00 were recorded as the light phase and 23:00, 03:00 and 07:00 were recorded as the dark phase.ResultsThe results showed that TVFA displayed a significant circadian rhythm following the introduction of the HS diet (p < 0.01). The concentration of TVFA (p < 0.01) and acetate (p < 0.01) were significantly higher during the light than the dark phase, regardless of diet type. PERMANOVA analysis revealed that diet and diet × time interaction strongly influenced the composition of duodenal microbiota. The relative abundance of Lachnospiraceae_ND3007_group showed a positive correlation with the propionate proportions under the HS diet during the light phase, while the HS diet significantly increased the abundance of Bifidobacterium and norank_f__Lachnospiraceae.ConclusionThese findings provide novel insights into diet-dependent circadian regulation of duodenal fermentation in dairy cattle.